Johne's Disease: where do we go from here? - Larry C. Hollis (Kansas Agricultural Experiment Station Research Reports, 2004)
Johne's disease was characterized as a significant disease in cattle before the start of the 20th century. The disease causes a chronic wasting away and non-responsive diarrhea, coupled with a long incubation period and difficulty in diagnosis until late in the course of disease. As a result, it has become a costly aggravation to dairy producers over the years. Of even greater concern, however, is the more recent incrimination of the causative agent, Mycobacterium avium subspecies pseudotuberculosis (MAP), as a possible cause of Crohn's disease in humans. Because MAP is present in milk of cows with advanced Johne's disease, and occasionally survives pasteurization, the dairy industry must work proactively to control this disease and reduce the potential for any associated human health risks.; Dairy Day, 2004, Kansas State University, Manhattan, KS, 2004;
Keywords: Dairy Day; 2004; Kansas Agricultural Experiment Station contribution; no. 05-112-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 941; Dairy; Johne& #x27; s Disease; Crohn& #x27; s Disease